2021
DOI: 10.3390/ijerph18084057
|View full text |Cite
|
Sign up to set email alerts
|

First Insight into Nutraceutical Properties of Local Salento Cichorium intybus Varieties: NMR-Based Metabolomic Approach

Abstract: Background: Plants of genus Cichorium are known for their therapeutic and nutraceutical properties determined by a wealth of phytochemical substances contained in the whole plant. The aim of this paper was to characterize the metabolic profiles of local Salento chicory (Cichorium intybus L.) varieties (“Bianca”, “Galatina”, “Leccese”, and “Otranto”) in order to describe their metabolites composition together with possible bioactivity and health beneficial properties. Methods: The investigation was performed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…In the tradition of many peoples, chicory is used for treating various health disorders. The studies on plants of the Cichorium genus have demonstrated many beneficial effects of the phytochemicals contained in the whole plant or parts of the plant, the potential utility and nutraceutical properties of the product, also providing a method to guarantee its authenticity at molecular scale (Girelli et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In the tradition of many peoples, chicory is used for treating various health disorders. The studies on plants of the Cichorium genus have demonstrated many beneficial effects of the phytochemicals contained in the whole plant or parts of the plant, the potential utility and nutraceutical properties of the product, also providing a method to guarantee its authenticity at molecular scale (Girelli et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…To identify compounds putatively involved in bioactivity, the complex water fractions, F5-8 were analyzed using NMR spectroscopy which is highly suitable for characterization of complex water extracts from plants [54][55][56][57] . Analysis of 1 H and 13 C spectra identified primary carbohydrates, malate, and choline, in all aqueous fractions.…”
Section: Discussionmentioning
confidence: 99%
“…The variables responsible for the observed discrimination were identified by using an S-line plot. Mean values ± standard deviation of selected and distinctive bucket reduced NMR signal areas (normalized to the total spectrum excluding the residual water region) were used to evaluate the relative change in discriminating metabolite content between the observed groups [ 16 ]. Log 2 fold change (FC) ratio of the normalized median intensity of the corresponding signals in the spectra of the groups was used to assess changes in metabolite level between two groups [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…This high throughput, reliable, non-invasive, high and reproducible technique provides quantitative and structural information on either specific molecules or complex mixtures [ 13 ], with minimal sample manipulation (typically just buffer addition) [ 15 ]. Thus, together with High Performance Liquid Chromatography coupled to Mass Spectroscopy (HPLC-MS), Nuclear Magnetic Resonance Spectroscopy (NMR) is widely used in metabolomic applications for food science and nutrition research [ [16] , [17] , [18] ]. In particular, the metabolomic approach based on NMR spectroscopy, has proven to be a powerful and reliable tool to obtain a simultaneous multiple-metabolites snapshot of biological samples for biomarker detection, food quality control, and/or origin discrimination [ 16 , [19] , [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%